Yun Casalilla, Bartolomé. Iberian World Empires and the Globalization of Europe 1415-1668. Palgrave-Macmillan/Palgrave Studies in Comparative Global History, 2019, pp. 546 - Sisto, Sebastián Daniel (2020)
Fil: Sisto, Sebastián Daniel. Universidad Nacional de La Plata.